The emergence and status of religious doctrines and sectarianism in Iraq - Viyan Abubakir Yasin; Shukr Abubakir Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research (The emergence and status of religious doctrines and sectarianism in Iraq) intensively discusses the political situation in Iraq amidst religious and sectarian conflicts and discusses the way of governing Iraq amidst the conflicts that have plagued the country in the past two decades in general As a result, the researcher concluded that the political process and statehood in Iraq is constantly in constant conflict and the presence of several different nationalities and several different religious sects are the main source of the problems faced by this country.